Model Ekonomi Leontief Pada Transaksi Domestik Terhadap Produktivitas Ekonomi Provinsi Jambi - Sholeh, Muhammad Quwwata; Panjaitan, Kevin Synagogue; Rungkati, Fatimah Qibtiyah; Multahadah, Cut (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Jambi Province, as a part of Indonesia, has an important role in contributing to the national economy. To understand economic dynamics in Jambi province, it is important to analyze domestic transactions on economic productivity. The aim of this research is to find out whether Jambi province's domestic transactions on economic productivity are productive or not, so that our research can be useful for policy makers. The method we use in analyzing the relationship between various economic sectors in Jambi province is to use the Leontief economic model, the results show the analysis by applying the results of the classification of the Jambi province domestic price transaction matrix which is modeled with the Leontief economic model using the reduction of the identity matrix with the results of the domestic price transaction matrix then the inverse results produce a negative matrix value, so it can be concluded that domestic transactions on the productivity of Jambi province are not productive. Therefore, each sector in each open unproductive sector refers to a part of a province's economy that does not make a significant contribution to economic growth or the welfare of society as a whole. Unproductive domestic transactions can harm the Jambi province's regional finances, so it is important to avoid them.